Scaling up breastfeeding in England through the Becoming Breastfeeding Friendly initiative (BBF). (4th November 2022) - Merritt, Rowena; Kendall, Sally; Eida, Tamsyn; Dykes, Fiona; Pérez‐Escamilla, Rafael
Abstract: Breastfeeding is the most accessible and cost‐effective activity available to public health and has been shown to be one of the most effective preventive measures mothers can take to protect their children's health. Despite the well‐documented benefits, the UK has one of the lowest breastfeeding rates in the world. The Becoming Breastfeeding Friendly (BBF) toolkit was developed through highly structured technical and academic collaboration, led by Yale University. It provides an evidence‐based process to help countries assess their breastfeeding status and readiness to scale up, and identifies concrete measures countries can take to sustainably increase breastfeeding rates, based on data‐driven recommendations. BBF is grounded in the Breastfeeding Gear Model complex adaptive systems framework which is made up of eight simultaneous conditions that sustain breastfeeding. In 2018, a committee of multi‐agency stakeholders implemented the BBF process in England, collecting evidence to score the 'gear' components of England's breastfeeding environment against 54 benchmarks. The Training and Programme Delivery gear received the highest score, attributable to existing learning outcomes for health professionals and practitioners, peer supporters and specialist services, although there is a need for greater coordination and integration. The lowest scores were given for Promotion and Coordination, Goals and Monitoring due to the lack of a dedicated national strategy for breastfeeding and poor sharing of localised strategies and programmes. The process generated clear recommendations highlighting the need for more robust routine infant feeding data collection and reporting, and the necessity for strengthening leadership, monitoring and oversight to scale up and sustain breastfeeding. Abstract : England has one of the lowest breastfeeding rates in the world. We used the Becoming Breastfeeding Friendly evidence‐based process to assess England's breastfeeding status and readiness to scale up, identifying concrete measures to sustainably increase breastfeeding rates based on data‐driven recommendations. Here we discuss England's need for more robust routine infant feeding data collection and reporting, and the necessity for strengthening leadership, monitoring and oversight to scale up and sustain breastfeeding. Key messages: England's overall weighted Becoming Breastfeeding Friendly (BBF) Index score was 1.1 (range 0–3) representing a moderate scaling up environment (range 1.1–2.0). Five gears: Political Will, Legislation and Policies, Funding and Resources; Training and Programme Delivery and Research and Evaluation scored at a moderate gear strength, while the remaining three gears— Advocacy, Promotion and Coordination Goals and Monitoring —were weak. The BBF process for England highlighted substantial gaps in the current breastfeeding practice data and recommended that more robust routine, population‐level infant feeding data collection and reporting is initiated that goes beyond 6–8 weeks and up to 2 years. The process identified that the lack of a national infant feeding co‐ordinator role or national breastfeeding committee had resulted in no dedicated workplan and a lack of advocacy for breastfeeding programmes. The need for greater future coordination, strategic goal setting and consistent monitoring was recommended to strengthen the breastfeeding environment.